EFL Interlanguage Experiences in Learning to Write Recount Text - Radatul Saidah; Yousef Bani Ahmad; Muhammad Reza Pahlevi (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Indonesia, interlanguage words are still very foreign, many second language students do not know the definition of these words. Interlanguage is a system of language that learners develop during L2 acquisition. Interlanguage is affected by the learner's native language as they use their native language knowledge to understand and organize the second language or to compensate for existing competency gaps. The purpose of this research is to find out the interlanguage experience that occurs when students write recount text. The research method uses a qualitative approach with narrative inquiry. As a result, there are three indicators that are the focus in examining students' experiences in writing recount text, as follows: L1 interference, overgeneralization, and simplification.